Cognitive and affective theory of mind in dementia with Lewy bodies and Alzheimer's disease. Issue 1 (December 2016) - Heitz, Camille; Noblet, Vincent; Phillipps, Clélie; Cretin, Benjamin; Vogt, Natacha; Philippi, Nathalie; Kemp, Jennifer; de Petigny, Xavier; Bilger, Mathias; Demuynck, Catherine; Martin-Hunyadi, Catherine; Armspach, Jean-Paul; et al.
Abstract Background Theory of mind (ToM) refers to the ability to attribute mental states, thoughts (cognitive component) or feelings (affective component) to others. This function has been studied in many neurodegenerative diseases; however, to our knowledge, no studies investigating ToM in dementia with Lewy bodies (DLB) have been published. The aim of our study was to assess ToM in patients with DLB and to search for neural correlates of potential deficits. Methods Thirty-three patients with DLB (DLB group) and 15 patients with Alzheimer's disease (AD group), all in the early stage of the disease, as well as 16 healthy elderly control subjects (HC group), were included in the study. After a global cognitive assessment, we used the Faux Pas Recognition (FPR) test, the Reading the Mind in the Eyes (RME) test and Ekman's Facial Emotion Recognition test to assess cognitive and affective components of ToM. Patients underwent cerebral 3-T magnetic resonance imaging, and atrophy of grey matter was analysed using voxel-based morphometry. We performed a one-samplet test to investigate the correlation between each ToM score and grey matter volume and a two-samplet test to compare patients with DLB impaired with those non-impaired for each test. Results The DLB group performed significantly worse than the HC group on the FPR test (P  = 0.033) and the RME test (P  = 0.015). There was no significant difference between the AD group and the HC group or between the DLB group and the AD group. Some brain regions were associated with ToM impairments. The prefrontal cortex, with the inferior frontal cortex and the orbitofrontal cortex, was the main region, but we also found correlations with the temporoparietal junction, the precuneus, the fusiform gyrus and the insula. Conclusions This study is the first one to show early impairments of ToM in DLB. The two cognitive and affective components both appear to be affected in this disease. Among patients with ToM difficulties, we found atrophy in brain regions classically involved in ToM, which reinforces the neuronal network of ToM. Further studies are now needed to better understand the neural basis of such impairment.